"Fear Is the Path to the Dark Side". Electoral Results and the Workplace Safety of Immigrants - Anna D'Ambrosio; Roberto Leombruni; Tiziano Razzolini (Institute of Labor Economics (IZA), 2021)
Populist parties' propaganda portrays immigrants as a threat to native workers' jobs. When propaganda materializes as an electoral success, it may drive changes in natives' attitudes towards immigrants. As shown experimentally by Bursztyn et al. (2020), electoral results may signal a change in social preferences about immigration and make individuals more likely to express anti-immigrant resentment that they were previously hiding. We employ Italian administrative data to explore whether this mechanism implies actual differences in native and foreign workers' labor market outcomes. We estimate the impact of the electoral results of an Italian populist party, the Lega Nord, on natives and foreigners' workplace injuries and wages. We show that, on average, a 1% increase in the votes for the Lega Nord increases within-job-spell injury rates of foreign workers by 0.9%. Firms below fifteen employees benefiting from less employment protection drive the result. We argue that this is due to a reallocation of hazardous tasks to immigrant workers only in contexts characterized by higher job insecurity. The evidence is weaker for wage reductions, arguably due to labor market rigidity.
Keywords: D72; J28; J71; 330; social norms; discrimination; workplace injuries